SAFETY OF PEDIATRIC COMBINATED VACCINE FOR DIPHTHERIA, PERTUSSIS, TETANUS, POLIO AND HAEMOPHILUS INFLUENZA TYPE B IN THE PRIMARY IMMUNIZATION AND FIRST BOOSTERISATION - N. D. Chernova; I. A. Ivanova; G. M. Demchuk; Y. E. Cousina; O. B. Valetova (Педиатрическая фармакология)
The results of studies of the safety of a combined five-component pediatric vaccine to prevent diphtheria, pertussis, tetanus, polio, Haemophilus influenzae type b (DTaP-IPV//Hib) in children in the primary vaccination and for the first boosterisation are shown. On the introduction of 208 doses of 264 (75.8%) there were no any local or general reactions registered. The registered local or general reactions occurred usually on the 1st day after vaccination and lasted for 1–2 days. Local reactions with a diameter ≥ 2 cm were reported in 2 cases (0.8%) and did not exceed the diameter of 2 cm. Increased body temperature ≥ 38,5°C was recorded in 3 cases (1.1%) and was not higher than 39,0°C. There have been fixed no cases of anaphylactic reactions, seizures, encephalitic reactions. Due to the high-profile security vaccine DTaP-IPV//Hib is suitable for wide application in outpatient conditions for the standard routine and catch-up vaccination of healthy children and children with underlying medical conditions.